2020
DOI: 10.1007/s42729-020-00190-5
|View full text |Cite
|
Sign up to set email alerts
|

Available Nitrogen in Paddy Soils Depth: Influence on Rice Root Morphology and Plant Nutrition

Abstract: Nitrogen (N) is a key nutrient for rice (Oryza sativa L.) and its availability in soil profile can influence the plant root morphology and total nutrient uptake. This study evaluated if N from deeper soil layers would increase rice root growth, N uptake and influence plant nutritional status. Flooded rice was grown in undisturbed soil samples from three locations with 15 N-labeled ammonium sulfate application at different depths (0, 10, 20, 30, and 45 cm). At rice heading, chlorophyll content and photosynthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 45 publications
(49 reference statements)
0
8
0
Order By: Relevance
“…Many researchers reported that deep placement of N fertilizer significantly enhanced the NUE and grain yield as compared with surface broadcasting (Miah et al 2016;Gaihre et al 2018;Yao et al 2018b). Deep placement of N fertilizer could substantially reduce the NH 4 + -N concentration in surface water but improve the soil NH 4 + -N contents (Ke et al 2018;Drescher et al 2020). Wang et al (2019) reported that reduced chemical fertilizer combined with straw retention could produce comparable grain yield to conventional rice production systems with surface broadcasting dose of NPK fertilizers.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers reported that deep placement of N fertilizer significantly enhanced the NUE and grain yield as compared with surface broadcasting (Miah et al 2016;Gaihre et al 2018;Yao et al 2018b). Deep placement of N fertilizer could substantially reduce the NH 4 + -N concentration in surface water but improve the soil NH 4 + -N contents (Ke et al 2018;Drescher et al 2020). Wang et al (2019) reported that reduced chemical fertilizer combined with straw retention could produce comparable grain yield to conventional rice production systems with surface broadcasting dose of NPK fertilizers.…”
Section: Introductionmentioning
confidence: 99%
“…Previous study showed that deep placement urea at 7-10 cm decreased the loss of urea compared with the broadcast urea method (Siddique et al 2020). and root growth of rice (Drescher et al 2020). Deep placement of N is generally an effective way to improve the ultilization of N fertilizer.…”
Section: Discussionmentioning
confidence: 99%
“…Rice plant prefers NH 4 + -N to NO 3 − -N as an N source ( 1 ). For Hapli type soil, the greater supply of NH 4 + -N in the subsoils might contribute to root growth and plant nutrition through an enhanced photosynthesis rate ( 55 ). The lower NH 4 + -N storage in Fe-accumuli soil might be attributable to the reduced N input provided by diazotrophs and high N loss mediated by denitrification.…”
Section: Discussionmentioning
confidence: 99%